The effectiveness of improving the quality of education through online platforms at higher education institutions in Kazakhstan (Gumilyov Journal of Pedagogy, 2025)
This article investigates the effectiveness of online platforms in education and suggests that they should be viewed as tools that enhance quality of language learning process. The importance of carefully examining various factors influencing the use of online platforms is immense. The primary purpose of this research is to conduct a comparative analysis of the implications of digital platforms on student engagement and learning outcomes compared to traditional educational methods. The data revealed implementation barriers, providing practical recommendations for integrating these educational language learning platforms into existing educational structures. Ultimately, this study can serve as a guide which updates educational institutions in Kazakhstan about the benefits and limitations of online platforms. The results contribute to a discussion on distance learning and digital learning innovations, while leveraging benefits of online platforms in education and addressing their challenges. It identifies the need to develop specific solutions that will impact the education landscape in Kazakhstan.